ANIMASI 3 DIMENSI SEBAGAI SARANA SOSIALISASI PENTINGNYA KECERDASAN EMOSIONAL DALAM KEHIDUPAN REMAJA - Ronald Tanga Ili Watun; Gde Lingga Ananta Kusuma Putra; Gede Pasek Putra Adnyana Yasa (Jurnal Bahasa Rupa, 2019)
In general, every human being must face problems and trials of life. There are various kinds of problems that come in life, do not know when, where and how these problems come. In dealing with problems, humans have their own ways to overcome these problems. There are those who give up easily and some who can overcome them. In this case the role of emotional intelligence is very important. Especially at the age of adolescence sometimes difficult to control emotions in themselves, resulting in a sense of hopelessness. Therefore, it is necessary to design a media that can be used to socialize the importance of emotional intelligence in adolescent life. The results showed that the concept that was appropriately used to socialize the importance of emotional intelligence in adolescents' lives was the concept of "Emotional Spirit". This concept was chosen to fit the objectives of this socialization as well as the intended target of youth. This 3D animated story was taken based on the true story of a teenager who was able to survive for 49 days in the middle of the ocean. In order for the socialization to run effectively, supporting media such as social media, posters, packaging, t-shirts, roll-up banners, stickers, tote bags and key chains are made. Through the design of the socialization media in the form of 3D animation along with its supporting media, it is expected that the target audience, namely adolescents, can better control their emotions when facing problems.